STUDI LITERATUR MANAJEMEN RISIKO HUKUM - Yanuardin Yanuardin (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2020)
Abstract: The bank as a financial institution that serves as a intermediary in its operational activitiesis not separated from the risks faced, the higher the risk, the more possible the profitability of abank. Sharia banks must have a range of preparation and strategy in risk management, starting fromthe goal setting phase and risk management strategy, identification, measurement and mitigationrisks, supervision, and the implementation of the risk management. According to PBI regulation No.13/25/PBI/2011 On the implementation of risk management for sharia banks and sharia businessunits, the risk is as potential as potential loss due to a particular perinstiwa. Legal risk is a risk arisingfrom lawsuits and the weakness of the juridical aspect is caused by the weakness of the Bank’salliance and the absence or change of regulation of banking invitation legislation. The Bank mustidentify and control the legal risks found in each of its functional activities.Keywords: Risk Management, Literature Study